2014
DOI: 10.1080/17470218.2013.793375
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Similarity in Updating Numerical Information in Working Memory: Decomposing the Numerical Distance Effect

Abstract: The present study investigates the process of updating representations in working memory (WM) and how similarity between the information involved influences this process. In WM updating tasks, the similarity in terms of numerical distance between the number to be substituted and the new one facilitates the updating process. We aimed to disentangle the possible effect of two dimensions of similarity that may contribute to this numerical effect: numerical distance itself and common digits shared between the numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…Previous work on updating declarative WM representations (as opposed to procedural task rules, see Oberauer, 2009) had primarily used verbal materials as stimuli, typically digits or letters (e.g., Artuso & Palladino, 2011Carretti, Cornoldi, & Pelegrina, 2007;Ecker, Lewandowsky, Oberauer, & Chee, 2010;Garavan, 1998;Kessler & Meiran, 2006Lendínez, Pelegrina, & Lechuga, 2014;Oberauer, 2003;Oberauer, Souza, Druey, & Gade, 2013; but see Ko & Seiffert, 2009;Manza et al, 2014;Souza, Rerko, & Oberauer, 2014 for exceptions using visual arrays). For example, Kessler and Meiran (2008) presented participants with a sequence of digit-sets.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work on updating declarative WM representations (as opposed to procedural task rules, see Oberauer, 2009) had primarily used verbal materials as stimuli, typically digits or letters (e.g., Artuso & Palladino, 2011Carretti, Cornoldi, & Pelegrina, 2007;Ecker, Lewandowsky, Oberauer, & Chee, 2010;Garavan, 1998;Kessler & Meiran, 2006Lendínez, Pelegrina, & Lechuga, 2014;Oberauer, 2003;Oberauer, Souza, Druey, & Gade, 2013; but see Ko & Seiffert, 2009;Manza et al, 2014;Souza, Rerko, & Oberauer, 2014 for exceptions using visual arrays). For example, Kessler and Meiran (2008) presented participants with a sequence of digit-sets.…”
Section: Introductionmentioning
confidence: 99%
“…A key issue when it comes to explaining success in WM updating tasks seems to relate to the availability of stored information, which depends on the ability to generate distinctive representations (e.g., Lendínez, Pelegrina, & Lechuga, 2011, 2013; Pelegrina et al, 2012). It is noteworthy that a clear and robust representation of the characteristics of an item is less important in some updating tasks, like the running memory span or the n-back tasks, because the updating criterion is only temporal.…”
mentioning
confidence: 99%
“…The current results appear inconsistent with findings that have studied the substitution component of updating specifically. For example, Lendínez et al (2011Lendínez et al ( , 2014 showed that similarity effects in the substitution process are beneficial to updating. However, it should be noted that they focused on the relation between old and new information.…”
Section: Discussionmentioning
confidence: 99%
“…When it is necessary to update a number that shares many features with another stored in memory, the process can be performed more quickly; fewer features of the second number need activation because shared features are already activated. As such, Lendínez et al (2011Lendínez et al ( , 2014 showed that updating RTs were faster when the distance between the number stored in memory and the number replacing it was smaller than when this distance was large. Indeed, they showed that the relation (based on numerical similarity) between old and new information involved in updating has an effect on RT.…”
mentioning
confidence: 97%